The female body and the law - Eisenstein, Zillah R. (UC Press voices revived., 2018)
The Female Body and the Law provides an original and incisive reexamination of the dynamics of sexual equality. Eisenstein contends that sexual inequality is fostered both by the law and by the insistence that men and women are biologically different. Through a fascinating discussion of a series of issues including affirmative action, AIDS, Baby M, pornography, and abortion, Eisenstein shows how the law operates as a political language that establishes.